Rehabilitation of Nonsyndromic Oligodontia in Deciduous Dentition Using Modified Hollywood Bridge - A Case Report - A K Safoora; Madhu Santhakumar; Kannan Vadakkepurayil (Indian Journal of Dental Research)
Oligodontia is a severe type of tooth agenesis involving six or more congenitally missing teeth, excluding the third molars. It is a rare condition and has a low prevalence in deciduous dentition. It can occur either as a part of syndromes or as a separate entity. This is a rare case report of a 3-year-old child with congenitally missing bilateral anterior and posterior deciduous teeth and its aesthetic and functional rehabilitation using a fixed appliance known as modified Hollywood bridge. In this appliance, molars are banded and acrylic teeth were secured to the stainless steel palatal wire with the help of heat cure acrylic resin. Modified Hollywood bridge provides a reasonable treatment option for the replacement of the missing deciduous teeth in children. It is more suitable for younger paediatric patients and also for physically or mentally handicapped patients.